2012
DOI: 10.1063/1.4767517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticle size, loading, and shape on the mechanical properties of polymer nanocomposites

Abstract: Articles you may be interested inEffects of size and interparticle interaction of silica nanoparticles on dispersion and electrical conductivity of silver/epoxy nanocomposites J. Appl. Phys. 115, 154307 (2014) Influence of nanoparticle size, loading, and shape on the mechanical properties of polymer nanocomposites We study the influence of spherical, triangular, and rod-like nanoparticles on the mechanical properties of a polymer nanocomposite (PNC), via coarse-grained molecular dynamics simulations. We focus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 43 publications
(116 reference statements)
1
54
0
Order By: Relevance
“…Insert Figure 12 here Nanoparticle size: Molecular dynamics simulations suggested that mechanical properties such as Young's and elastic modulus of NP-containing polymer composites improved with decreasing particle size at a constant NP concentration [213,214]. Reinforcement by NPs depends on the particle-polymer contact surface area [213].…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…Insert Figure 12 here Nanoparticle size: Molecular dynamics simulations suggested that mechanical properties such as Young's and elastic modulus of NP-containing polymer composites improved with decreasing particle size at a constant NP concentration [213,214]. Reinforcement by NPs depends on the particle-polymer contact surface area [213].…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…We observed better mobility and higher deformation resistance in gum arabic nanoparticles, thus indicating that they may play an important role in increasing the internal cohesion strength of the sundew-inspired adhesive hydrogels. 40,41 Besides the nanoparticles’ functions in strengthening the internal strength of the cohesion zone, gum arabic nanoparticles may contribute to the anisotropic nanostructures of the nanocomposite adhesive.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the main objective of this study is using a powerful method to optimize material and processing conditions in the twin-screw compounding of PA-6/NC nanocomposites and evaluating their effects on mechanical properties which is not considered in detail in other reports. Moreover, notwithstanding the vast number of papers concerning PNCs, a few works have been devoted to investigate modeling the effect of different parameters on PNC mechanical properties [36,37]. More importantly, the studies that have dealt with mechanical properties were barely systematic, using the inefficient one-factor-at-atime (OFAT) approach and missing the interaction between factors.…”
Section: Introductionmentioning
confidence: 98%